Body and balance - increasing sprint speed with the arms - Thomas, S. (Techniques Magazine, 2023)
Coaching Athletics (Track & Field) is about solving problems with movement. All correct movements will apply the greatest force in the shortest period of time. So, the solution to all problems in Athletics is maximum force generation as fast as possible. The first objective in Athletics is maximum force development. Once this is developed, speed of application becomes the priority. The coach and sprinter must understand that speed is not a feeling, but a creation. Feeling speed by moving the arms and feet fast does not produce speed, it produces the feeling of speed. Speed is created by applying maximum force to the ground in the shortest time. In sprinting, the athlete hat .08-.10 to maximize force into the ground. Coaches must understand that the athlete runs on their legs, but they sprint with their arms. Force acts on the human body at the center mass or center of gravity.